One-Dimensional Plasmonic Sensors - Liu, Yitian; Ma, Yaoguang (Frontiers in Physics, 2020)
Recent advances in surface plasmon sensors have significantly reduced the limitations of conventional optical sensors. With the recent development of micro- and nano-fabrication technology, miniaturized one-dimensional structures become a promising platform for surface plasmon sensors for its compactness and simple structure. In this review, we describe the generation of surface plasmon polaritons and the resonance conditions. Then we categorize surface plasmon sensors by the physical quantities they detect, elaborating their working principle, performance, and current development. Finally, we summarize both limitations and advances of various design methods to provide an outlook on future directions of this field.